2015
DOI: 10.1016/j.bbamcr.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced amino acid utilization sustains growth of cells lacking Snf1/AMPK

Abstract: The metabolism of proliferating cells shows common features even in evolutionary distant organisms such as mammals and yeasts, for example the requirement for anabolic processes under tight control of signaling pathways. Analysis of the rewiring of metabolism, which occurs following the dysregulation of signaling pathways, provides new knowledge about the mechanisms underlying cell proliferation. The key energy regulator in yeast Snf1 and its mammalian ortholog AMPK have earlier been shown to have similar func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 49 publications
3
39
1
Order By: Relevance
“…This phenotype highlights the importance of SNF1 at low glucose concentrations. However, it was also reported that at 2% glucose, snf1Δ cells grown in synthetic medium showed similar glucose consumption as the WT strain (BY4741), but glucose consumption increased at 5% concentration, relative to the WT strain (Nicastro et al, ). Differences from previous reports could be due to the different medium used.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This phenotype highlights the importance of SNF1 at low glucose concentrations. However, it was also reported that at 2% glucose, snf1Δ cells grown in synthetic medium showed similar glucose consumption as the WT strain (BY4741), but glucose consumption increased at 5% concentration, relative to the WT strain (Nicastro et al, ). Differences from previous reports could be due to the different medium used.…”
Section: Discussionmentioning
confidence: 90%
“…However, a clear relationship between the Crabtree effect and Snf1p has not been found yet. Cell glucose uptake is the main factor associated with the Crabtree effect and is regulated by hexose transporters mainly (Huberts et al, ), and in turn, the Snf1p/Mig1p pathway regulates transcriptionally some hexose transporters (Kuttykrishnan, Sabina, Langton, Johnston, & Brent, ; Nicastro et al, ). These data imply that Snf1p could regulate the glycolytic flux and the Crabtree effect, and our results support this idea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect possible new targets of Snf1, we chose to use a co-immunoprecipitation/MS approach, immunoprecipitating myc-tagged Snf1 and detecting co-immunoprecipitated proteins with mass spectrometry after resolution with SDS-PAGE. We performed this experiment with protein extracts of exponentially growing cells in 2% glucose, because we already demonstrated that in this condition Snf1 is at least partially functional (22,25).…”
Section: Snf1mentioning
confidence: 99%
“…In response to high glucose concentrations, Snf1 is inactivated through dephosphorylation of Thr 210 by the Glc7 protein phosphatase (also known as PP1), which is targeted to Snf1 by the adaptor subunit Reg1 (20,21). However, recent studies highlighted Snf1 function also in glucose-repressed conditions, as well as its partial activation and its role in the regulation of cell cycle (22)(23)(24)(25). The most studied function of Snf1 is the regulation of transcription, involving more than 400 genes (26).…”
mentioning
confidence: 99%